Phenomenology of the Cultural Disciplines
VIII, 346 p.
Keywords: Phenomenology of the Cultural Disciplines is an interdisciplinary study, reflecting the recent emergence of various particular forms of `phenomenological philosophy of ...'. Included are such fields as psychology, social sciences and history, as well as environmental philosophy, ethnic studies, religion and even more practical disciplines, such as medicine, psychiatry, politics, and technology. The Introduction provides a way of understanding how these various developments are integrated. On the basis of a Husserlian notion of culture, it proposes a generic concept of `cultural disciplines' (which is broader than but inclusive of `human sciences') which subsumes the more specific concepts of `cultural sciences', `axiotic disciplines' (e.g. architecture), and `practical disciplines'.